Mechanisms that match ATP supply to demand in cardiac pacemaker cells during high ATP demand - Yaniv, Yael; Spurgeon, Harold A; Ziman, Bruce D; Lyashkov, Alexey E; Lakatta, Edward G (American journal of physiology. Heart and circulatory physiology, 2013)
The spontaneous action potential (AP) firing rate of sinoatrial node cells (SANCs) involves high-throughput signaling via Ca(2+)-calmodulin activated adenylyl cyclases (AC), cAMP-mediated protein kinase A (PKA), and Ca(2+)/calmodulin-dependent protein kinase II (CaMKII)-dependent phosphorylation of SR Ca(2+) cycling and surface membrane ion channel proteins. When the throughput of this signaling increases, e.g., in response to β-adrenergic receptor activation, the resultant increase in spontaneous AP firing rate increases the demand for ATP. We hypothesized that an increase of ATP production to match the increased ATP demand is achieved via a direct effect of increased mitochondrial Ca(2+) (Ca(2+)m) and an indirect effect via enhanced Ca(2+)-cAMP/PKA-CaMKII signaling to mitochondria. To increase ATP demand, single isolated rabbit SANCs were superfused by physiological saline at 35 ± 0.5°C with isoproterenol, or by phosphodiesterase or protein phosphatase inhibition. We measured cytosolic and mitochondrial Ca(2+) and flavoprotein fluorescence in single SANC, and we measured cAMP, ATP, and O₂ consumption in SANC suspensions. Although the increase in spontaneous AP firing rate was accompanied by an increase in O₂ consumption, the ATP level and flavoprotein fluorescence remained constant, indicating that ATP production had increased. Both Ca(2+)m and cAMP increased concurrently with the increase in AP firing rate. When Ca(2+)m was reduced by Ru360, the increase in spontaneous AP firing rate in response to isoproterenol was reduced by 25%. Thus, both an increase in Ca(2+)m and an increase in Ca(2+) activated cAMP-PKA-CaMKII signaling regulate the increase in ATP supply to meet ATP demand above the basal level.